Seaweed Loads Cause Stronger Bacterial Community Shifts in Coastal Lagoon Sediments Than Nutrient Loads - Aires, Tânia; Muyzer, Gerard; Serrão, Ester A.; Engelen, Aschwin H. (Frontiers in Microbiology, 2019)
The input of nutrients from anthropogenic sources is the leading cause of coastal eutrophication and is usually coupled with algal/seaweed blooms. Effects may be magnified in semi-enclosed systems, such as highly productive coastal lagoon ecosystems. Eutrophication and seaweed blooms can lead to ecosystem disruption. Previous studies have considered only one of these factors, disregarding possible interactive effects and the effect of the blooming species’ identity on sediment bacterial communities. We tested the effect of experimental nutrient loading and two common blooming seaweeds (Ulva rigida and Gracilaria vermiculophylla) in coastal lagoon sediments, on the structure of bacterial communities (using 16S rRNA amplicon sequencing) and corresponding putative functional potential (using PiCRUSt). At the Operational Taxonomic Unit (OTU) level, the addition of nutrients reduced bacterial community α-diversity and decreased the abundance of sulfate reducers (Desulfobacterales) compared to sulfur oxidizers/denitrifiers (Chromatiales and Campylobacterales), whereas this was not the case at the order level. Seaweed addition did not change bacterial α-diversity and the effect on community structure depended on the taxonomic level considered. The addition of Gracilaria increased the abundance of orders and OTUs involved in sulfate reduction and organic matter decomposition (Desulfobacterales, Bacteroidales, and Clostridiales, respectively), an effect which was also detected when only Ulva was added. Nutrients and the seaweeds combined only interacted for Ulva and nutrients, which increased known sulfide oxidizers and denitrifiers (order Campylobacterales). Seaweed enrichment affected putative functional profiles; a stronger increase of sulfur cycling KEGG pathways was assigned to nutrient-disturbed sediments, particularly with the seaweeds and especially Ulva. In contrast, nitrogen and sulfur cycle pathways showed a higher abundance of genes related to dissimilatory nitrate reduction to ammonium (DNRA) in Ulva+nutrients treatments. However, the other seaweed treatments increased the nitrogen fixation genes. Thiosulfate reduction, performed by sulfate-reducing bacteria, increased in seaweed treatments except when Ulva was combined with nutrients. In conclusion, the in situ addition of nutrients and the seaweeds to intertidal sediments affected the bacterial communities differently and independently. The predicted functional profile suggests a shift in relative abundances of putative pathways for nitrogen and sulfur cycles, in line with the taxonomic changes of the bacterial communities.